2003
DOI: 10.1093/jb/mvg010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitogen-Activated Kinase Kinase Kinase 3 Activity through Phosphorylation by the Serum- and Glucocorticoid-Induced Kinase 1

Abstract: The mitogen-activated protein kinase kinase kinase 3 (MEKK3) is a member of the MAP kinase family whose cellular activity is elevated in response to growth factors, oxidative stress, and hyperosmolar conditions. MEKK3 regulates MKK3 and MKK5/6/7. MEKK3 is involved distinctively in the signal pathway for blocking cell proliferation and cell cycle progression, contradictory to the biological responses commonly associated with other members of MEKKs. Based information concerning the substrate specificity of serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The identification and characterization of SGK1 substrates may provide clues to our understanding of how SGK1 contributes to cell survival and death (3,4,8,10,11,18). We demonstrated that Fe65 is a SGK1 substrate that contains the consensus motif RxRxxS/Tφ: where φ is a hydrophobic amino acid, which subsequently demonstrated that phosphorylation of Fe65 by SGK1 controls its subcellular localization (Figs.…”
Section: Ser Fe65mentioning
confidence: 78%
See 2 more Smart Citations
“…The identification and characterization of SGK1 substrates may provide clues to our understanding of how SGK1 contributes to cell survival and death (3,4,8,10,11,18). We demonstrated that Fe65 is a SGK1 substrate that contains the consensus motif RxRxxS/Tφ: where φ is a hydrophobic amino acid, which subsequently demonstrated that phosphorylation of Fe65 by SGK1 controls its subcellular localization (Figs.…”
Section: Ser Fe65mentioning
confidence: 78%
“…After electrophoresis, the gel was photographed on a transilluminator. The optical density of the phosphorylated product was measured by densitometry (10,22).…”
Section: Phosphorylation Of Recombinant Fe65mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the mitogen-activated protein kinase kinase kinase 3 (MEKK3) has been shown to be a target substrate for SGK (7). MEKK3 lies upstream of mitogen-activated protein kinase kinase (MKK) 3 and 6, which are activators of p38 MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…SGK mediates cell cycle progression (8,11) and transmembrane ion and metabolite transport (30). SGK is involved in osmotic cell adaptation via regulation of epithelial Na ϩ channels in kidney-collecting duct (A6) cells (49).…”
mentioning
confidence: 99%